Universal Health Coverage in Developing Countries: Barriers and Strategic Reforms - Syaddam , Multy Multy (Journal of Health Literacy and Qualitative Research, 2021)
Achieving Universal Health Coverage (UHC) in developing countries remains a significant challenge due to financial constraints, inadequate healthcare infrastructure, governance inefficiencies, and socio-economic disparities. This study systematically reviews existing literature to examine key barriers and potential solutions to UHC implementation in low- and middle-income countries (LMICs). A comprehensive search of PubMed, Scopus, and other academic databases was conducted to identify relevant peer-reviewed studies published within the past decade. The findings reveal that financial limitations, including high out-of-pocket expenditures and inefficient health financing models, continue to restrict healthcare access. Additionally, infrastructural gaps, healthcare workforce shortages, and governance issues exacerbate disparities in service delivery, particularly in rural and marginalized populations. Despite these barriers, strategies such as integrated healthcare models, targeted subsidies, public-private partnerships, and digital health innovations have demonstrated potential in improving UHC outcomes. However, the effectiveness of these interventions depends on sustained political commitment, efficient policy implementation, and continuous investment in health system resilience. This review underscores the need for context-specific approaches to UHC financing, regulatory frameworks, and service delivery models that prioritize equity and sustainability. Future research should explore comparative analyses of successful UHC models and evaluate the long-term impacts of digital health interventions to inform evidence-based policy decisions.